Privacy of information in qualitative social research: the transition to the digital world - Rapimán Salazar, María Eugenia; Chibey Rivas, Tamara Jesús (Acta Bioethica, 2022)
This text addresses the problem of information privacy in qualitative social research developed in the context of the digital world. For this purpose, the concept of privacy is reviewed from an analogical view towards its incorporation in the digital plane with the figure of information privacy and some elements of Gadamer’s hermeneutics. First, the analogical and ethical plane of privacy is reviewed. Then, the potential of information, the distinction between private and sensitive information and its applicability to social research through the concepts of trust and security are reviewed. Finally, we outline a proposal for a renewed privacy that proposes to rescue the intersubjectivity that is built in the relationship between the research participant and the researcher.